TLR7 promotes chronic airway disease in RSV-infected mice - Miles, Mark A.; Liong, Stella; Liong, Felicia; Coward-Smith, Madison; Trollope, Gemma S.; Oseghale, Osezua; Erlich, Jonathan R.; Brooks, Robert D.; Logan, Jessica M.; Hickey, Shane; Wang, Hao; Bozinovski, Steven; et al. (Frontiers in Immunology, 2023)
Respiratory syncytial virus (RSV) commonly infects the upper respiratory tract (URT) of humans, manifesting with mild cold or flu-like symptoms. However, in infants and the elderly, severe disease of the lower respiratory tract (LRT) often occurs and can develop into chronic airway disease. A better understanding of how an acute RSV infection transitions to a LRT chronic inflammatory disease is critically important to improve patient care and long-term health outcomes. To model acute and chronic phases of the disease, we infected wild-type C57BL/6 and toll-like receptor 7 knockout (TLR7 KO) mice with RSV and temporally assessed nasal, airway and lung inflammation for up to 42 days post-infection. We show that TLR7 reduced viral titers in the URT during acute infection but promoted pronounced pathogenic and chronic airway inflammation and hyperreactivity in the LRT. This study defines a hitherto unappreciated molecular mechanism of lower respiratory pathogenesis to RSV, highlighting the potential of TLR7 modulation to constrain RSV pathology to the URT.